Into the Deep - Coble, Colleen (Nashville : Thomas Nelson, 2013)
A local scientist turns up dead in Lake Superior. A radical environmental group blames a mysterious lab for the dead fish found in a remote stream. Then an Alzheimer's patient goes missing and his home is ransacked. A canine search-and-rescue team must help unravel the secrets of an enchanting wilderness.
Keywords: Upper Peninsula (Mich.) -- Fiction; Suspense fiction; Christian fiction; Mystery fiction